2021
DOI: 10.3389/fphar.2021.671152
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Chinese Medicine JY5 Formula Alleviates Hepatic Fibrosis by Inhibiting the Notch Signaling Pathway

Abstract: Advanced liver fibrosis can lead to cirrhosis, resulting in an accelerated risk of hepatocellular carcinoma and liver failure. Fuzheng Huayu formula (FZHY) is a traditional Chinese medicine formula treated liver fibrosis in China approved by a Chinese State Food and Drug Administration (NO: Z20050546), composed of Salvia Miltiorrhiza bge., Prunus davidiana (Carr.) Franch., cultured Cordyceps sinensis (BerK.) Sacc. Mycelia, Schisandra chinensis (Turcz.) Baill., Pinus massoniana Lamb., and Gynostemma pentaphyllu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…In the CCl 4 -and BDL-induced hepatic fibrosis rat experiment, after treatment with JY5 (salvianolic acid B: 16 mg/kg, schisantherin A: 2 mg/kg, amygdalin: 0.5 mg/kg), significantly alleviated hepatic injury and collagen deposition, the expressions of Jagged1, Notch2, Notch3, Notch4 and recombination signal binding protein-κB (RBP-κB) were significantly decreased. Meanwhile, consistent results were obtained in CCl 4 -induced hepatic fibrosis in mice, after JY5 (salvianolic acid B, 16 mg/kg amygdalin, 0.5 mg/kg schisantherin A, 2 mg/kg) treatment (Fu et al, 2021). These results suggest that JY5 could significantly inhibit the activation of Notch signaling pathway in CCl 4 -and BDL-induced liver fibrosis.…”
Section: Traditional Applications Of Tcms Against Hepatic Fibrosissupporting
confidence: 76%
See 2 more Smart Citations
“…In the CCl 4 -and BDL-induced hepatic fibrosis rat experiment, after treatment with JY5 (salvianolic acid B: 16 mg/kg, schisantherin A: 2 mg/kg, amygdalin: 0.5 mg/kg), significantly alleviated hepatic injury and collagen deposition, the expressions of Jagged1, Notch2, Notch3, Notch4 and recombination signal binding protein-κB (RBP-κB) were significantly decreased. Meanwhile, consistent results were obtained in CCl 4 -induced hepatic fibrosis in mice, after JY5 (salvianolic acid B, 16 mg/kg amygdalin, 0.5 mg/kg schisantherin A, 2 mg/kg) treatment (Fu et al, 2021). These results suggest that JY5 could significantly inhibit the activation of Notch signaling pathway in CCl 4 -and BDL-induced liver fibrosis.…”
Section: Traditional Applications Of Tcms Against Hepatic Fibrosissupporting
confidence: 76%
“…Moreover, FZHY dramatically elevated the expression of Hexokinase 2 (Hk2) and glutamine synthetase (Gs), regulated the both glucose metabolism and amino acid metabolism as well as reduced dehydrogenase 1 (Adh1), acetyl-CoA synthetase 2 (Acss2) and glutamic-pyruvictransaminase (Gpt) ( Hu et al, 2019 ), suggested FZHY has good anti-hepatic fibrosis effect via altering the metabolic pathways. Fu et al (2021) found a novel Chinese medicine, namely JY5 formula, composed of salvianolic acid B, schisantherin A and amygdalin, the main active ingredients of FZHY, and evaluated its anti-hepatic fibrosis activity both in vitro and in vivo . In the CCl 4 -and BDL-induced hepatic fibrosis rat experiment, after treatment with JY5 (salvianolic acid B: 16 mg/kg, schisantherin A: 2 mg/kg, amygdalin: 0.5 mg/kg), significantly alleviated hepatic injury and collagen deposition, the expressions of Jagged1, Notch2, Notch3, Notch4 and recombination signal binding protein-κB (RBP-κB) were significantly decreased.…”
Section: Traditional Applications Of Tcms Against Hepatic Fibrosismentioning
confidence: 99%
See 1 more Smart Citation
“…It has nephroprotective effects in both glycerol-induced acute renal failure and adenine-induced chronic renal failure rats (Ngai et al, 2005). Cordyceps-related formulations of Novel JY5 formula (Fu et al, 2021), CGA formula Tian et al, 2019), and Fuzheng Huayu formula (Chen et al, 2019b) all have good effects against liver fibrosis, suggesting that these formulations may also be potential novel therapeutic candidates for RF.…”
Section: Clinical Studies Of Cordyceps and Related Products In Treati...mentioning
confidence: 99%
“…Recently, the anticancer effects of Sal-B have been demonstrated in human cancer cell lines and in vitro studies have shown that Sal-B induces cell death and promotes apoptosis. Fu et al (2021) found a key factor in the ability of Sal-B to induce cell death is the promotion of autophagy and apoptosis in tumor cells. Moreover, Gong et al showed that Sal-B-induced cell death was associated with AKT/mTOR signaling inhibition (Gong et al, 2016).…”
Section: Sal-b Inhibits Human Hepatocellular Carcinoma Cell Viabilitymentioning
confidence: 99%